EFFECT OF QUALITY AND FREQUECY OF DRINKING WATER ON PRODUCTIVITY AND FERTILITY OF DAIRY BUFFALOES - R. Khan; M. S. Qureshi; A. Mushtaq; Ghufranullah; A. Naveed (Journal of Animal and Plant Sciences, 2012)
The present study was conducted to evaluate the mineral and heavy metal content in drinking water and document its effect on productivity performance of dairy buffaloes. Twenty five dairy farms were selected having 10 to 122 buffaloes. Data were collected regarding milk yield, body condition score (BCS) and services per conception (SPC). Representative samples were collected from the water used for the dairy animals. One liter water samples were collected from each of the dairies drinking troughs and analyzed for Ca, Mg, Fe, Zn, Cu, Mn, Cd, Cr, and Pb. Water analysis was performed by atomic absorption spectrophotometry. Milk yield was positively affected by Mn and negatively by Fe, Zn and Pb. BCS was adversely affected by Fe and Mg, and positively by Zn and Cd. Iron in drinking water significantly (P<0.05) reduced milk yield, body condition score and increase services per conception. The watering frequency negatively affected milk production and BCS (P<0.01) while significantly increasing SPC (P<0.05). It is concluded that free access to drinking water positively affected milk yield, body condition and fertility. An increase in body condition was noted with higher Zn intake in the drinking water. The higher intake of lead was associated with depressed milk yield. The present study clearly shows the importance of water quality in dairy animals. For quality food products for human consumption, appropriate legislation are required for drinking water used for livestock rearing and quality monitoring of food products.
Keywords: Heavy metals; minerals; drinking water; Buffaloe and BCS